Perkembangan Wisata Alam Bantimurung Dalam Prespektif Sejarah dan Budaya - Arnita Vitasari; Jumadi; Patahuddin; Syamsu Rijal (Politeknik Pariwisata Makassar, Indonesia, 2021)
This study aims to determine the background of Bantimurung including the Bantimurung-Bulusaraung National Park, the development of Bantimurung as a tourist attraction and the impact of the presence of the Bantimurung Nature Tourism Area in 2000-2018. This research is a historical research with a historical methodology that has stages namely, heuristics (data collection), criticism (verification), interpretation (interpretation) and historiography (history writing). The results of this study indicate that the background of Bantimurung enters the Bantimurung-Bulusaraung National Park, because Bantimurung is a natural area with beautiful scenery that must be protected. Development of the Bantimurung Nature Tourism Area continues to experience development and continue to explore what is in this area including the objects in it. Various efforts have been made by the Department of Tourism both in developing infrastructure and detailed administrative arrangements. The presence of this tourist attraction is as a forum for the community around Maros Regency to support the economy, a place for students to research and become a place of recreation for all people.